Medical Diagnoses with a Cartographic Oriented Model - Carvalho, Elizabeth, Simão (2012)
The human body is composed of several systems and organs that have a specific and well located position within it. Each organ is usually related to one or more physiological data. There is a subtle spatial interdependency on human’s body structure and behaviour. Because of this, doctors usually execute a spatial analysis when diagnosing a disease in a patient. The doctor has to combine patient’s medical data performing some “implicit” algebraic map operation. Although this is true, most of the models used to analyze, to process and to visualize these data, do not take into account the strong spatial interdependency inherent to human body’s functioning. These models usually treat morphological and physiological data in a full autonomous and isolated way. This happens because they are not “spatially” oriented, and do not interpret the human body as a 3D map, being composed by different parts and layers of information. The possibility of combining these layers using spatial algebraic operations, introduces a new degree of information insight. The main goal of the CHUB (Cartographic Human Body) model is to introduce a cartographic approach to help doctors to analyse, visualize and diagnosis human’s body illnesses.